Odpowiedź :
Odpowiedź:
a=1 b=-1 c=-6
Δ= b²-4ac= 1+24=25 √Δ=5
x1=(-b-√Δ)/2a= ( 1-5)/2=-2
x2=(-b+√Δ)/2a=( 1+5)/2=3
2]
a= 4 b=-7 c=-2
Δ= 49+ 32= 81 √Δ=9
x1=( 7-9) /8= - 1/4 x2=( 7+9)/8= 2
Szczegółowe wyjaśnienie:
Odpowiedź:
1.
x²-x-6=0
Δ=b²-4ac a=1, b=-1 c=-6
Δ=(-1)²-4×1×(-6)=25
[tex]\sqrt{}[/tex]Δ=5
[tex]x_{1}[/tex]=[tex]\frac{-b+\sqrt{D}}{2a}[/tex] ∪ [tex]x_{2}[/tex] =[tex]\frac{-b-\sqrt{D} }{2a}[/tex]
[tex]x_{1}[/tex]=3 ∪ [tex]x_{2}[/tex] =-2
2. a=4, b=-7, c=-2
Δ=49-4×4×(-2)=81
√Δ=9
[tex]x_{1}[/tex]=-[tex]\frac{1}{4}[/tex] ∪ [tex]x_{2}[/tex]=2
Szczegółowe wyjaśnienie: